NOVELTIES IN HERITIERA DRY. AND SCAPHIUM SCHOTT & ENDL. (STERCULIACEAE) - KOSTERMANS, A.J.G.H. (REINWARDTIA, 1988)
Heritiera magnifica Kosterm. and Scaphium velutinosum Kosterm. are described as new species based on specimens collected in Sumatra and Borneo respectively.